Global filtered tropospheric NO2 slant column densities derived from 6-year averages of TROPOMI measurements over water for shipping signal detection - Miriam Latsch; Andreas Richter; John Philipp Burrows; Hartmut Bösch (PANGAEA, 2025)
This dataset contains 6-year averages of global filtered tropospheric NO2 slant column densities (tSCDs) retrieved from the Sentinel-5 Precursor (S5P) satellite sensor TROPOMI (Tropospheric Monitoring Instrument) for the period from 1 May 2018 to 30 April 2024. All data are available on a 0.03° x 0.03° grid. The NO2 tSCDs are derived from the total slant columns by subtracting the across-track NO2 slant column stripe offset and spatially averaged stratospheric vertical column densities (VCDs) multiplied with the stratospheric air mass factor (AMF), provided in the TROPOMI NO2 product. The filtered NO2 tSCDs are developed to detect global shipping signals in the NO2 TROPOMI data. Therefore, only pixels over water are available in this dataset. The filtering methods include a high-pass filter with different box sizes (1°, 0.5°, 0.25°) and a Fourier filter. In addition, different flagging criteria are applied to the data with the standard box size of 1° for the high-pass filtering: no flagging, quality (qa) flagging, cloud fraction (CF) flagging, cloud height (CH) flagging, wind speed (wind) flagging, and sun glint (sg) flagging.